The Relationship Of Demand Utilization Of Health Service With Patient Satisfaction At Inpatient Care Unit Of Anuntaloko General Hospital - Oktania, Dwi Sitti (Tadulako University, 2019)
Hospital is a comprehensive form of health service institution, includes aspects of promotive, preventive, curative and rehabilitation, as well as a public health referral center. Demand on healthcare service theory consists of revenue, visit cost andÂ service quality. Anuntaloko Regional General Hospital Parigi Moutong Regency is a referral center and regionalization hospital in Central Sulawesi Province, which the number of visits in 2016 to 2018 in a row were 19.186, 10.971 and 12.954. The study was purposed to determined Relation Between Requests for Use of Health Service and Patient Satisfaction on Inpatient Care Unit at Anuntaloko Regional General Hospital Parigi Moutong Regency. This was a quatitative analysis research with the cross sectional study approach. The population was patients on Inpatient Care Unit of Anuntaloko Regional General Hospital which amounted to 12.954 sampels and through purposive sampling technique. Data was analyzed univariate and bivariate variables using Chi-Square Test. The results showed that there are relation between revenue (p=0,002), visit cost (p=0,002) and service quality (p=0,000) with patients satisfaction on Inpatient Care Unit at Anuntaloko Regional General Hospital Parigi Moutong Regency. The Anuntaloko Regional General Hospital Parigi Moutong Regency is expected to observe routinly so that maintaining the service quality of the good things and improving the service quality of the lack variabels. Â